Upaya Meningkatkan Hasil Belajar Siswa dengan Menggunakan Strategi Learning Tournament - Hamidah, Aah; Endang, Ujang (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2016)
Civics learning process in Public Elementary School (SDN) Bayusetra take place in the absence of innovative use of learning strategies that result in the student being bored to absorb the lessons delivered by teachers and influence the learning outcomes to be low. Application of tournament- learning oriented to maximize active learning in small groups of students and create a learning climate that is effective, proven to improve student learning outcomes characterized by an increase in per cycle of three study cycles.